Role for Actin Filament Turnover and a Myosin II Motor in Cytoskeleton-driven Disassembly of the Epithelial Apical Junctional Complex - Ivanov, Andrei I. (The American Society for Cell Biology, 2004)
Disassembly of the epithelial apical junctional complex (AJC), composed of the tight junction (TJ) and adherens junction (AJ), is important for normal tissue remodeling and pathogen-induced disruption of epithelial barriers. Using a calcium depletion model in T84 epithelial cells, we previously found that disassembly of the AJC results in endocytosis of AJ/TJ proteins. In the present study, we investigated the role of the actin cytoskeleton in disassembly and internalization of the AJC. Calcium depletion induced reorganization of apical F-actin into contractile rings. Internalized AJ/TJ proteins colocalized with these rings. Both depolymerization and stabilization of F-actin inhibited ring formation and disassembly of the AJC, suggesting a role for actin filament turnover. Actin reorganization was accompanied by activation (dephosphorylation) of cofilin-1 and its translocation to the F-actin rings. In addition, Arp3 and cortactin colocalized with these rings. F-actin reorganization and disassembly of the AJC were blocked by blebbistatin, an inhibitor of nonmuscle myosin II. Myosin IIA was expressed in T84 cells and colocalized with F-actin rings. We conclude that disassembly of the AJC in calcium-depleted cells is driven by reorganization of apical F-actin. Mechanisms of such reorganization involve cofilin-1-dependent depolymerization and Arp2/3-assisted repolymerization of actin filaments as well as myosin IIA-mediated contraction.